2019
DOI: 10.1002/admi.201900646
|View full text |Cite
|
Sign up to set email alerts
|

Structure of Nonsolvent‐Quenched Block Copolymer Solutions after Exposure to Electric Fields during Solvent Evaporation

Abstract: In this work, an electric field is incorporated during the solvent evaporation step of the block copolymer self‐assembly and nonsolvent induced phase separation (SNIPS) process. This study investigates the structure of nonsolvent‐quenched polystyrene‐block‐poly(2‐vinylpyridine) (PS‐b‐P2VP) and polystyrene‐block‐poly(4‐vinylpyridine) (PS‐b‐P4VP) diblock copolymer solutions after exposure to electric fields during solvent evaporation. The results indicate an emphasizing effect of the electric field, enhancing se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 62 publications
2
26
0
1
Order By: Relevance
“…The development of the cross-sectional morphology for a PS- b -P4VP membrane with increasing evaporation time is presented in (b). Reproduced with permission from ref . Copyright 2017 John Wiley & Sons Ltd.…”
Section: Evaporation-induced Self-assembly Followed By Non-solvent-in...mentioning
confidence: 99%
“…The development of the cross-sectional morphology for a PS- b -P4VP membrane with increasing evaporation time is presented in (b). Reproduced with permission from ref . Copyright 2017 John Wiley & Sons Ltd.…”
Section: Evaporation-induced Self-assembly Followed By Non-solvent-in...mentioning
confidence: 99%
“…The cylindrical progression of pores in a micellar solution having a spherical initial state is the result of coalescence of spheres layer by layer during solvent evaporation [39]. This phenomenon can also be facilitated by increasing the segregation strength, e.g., by selective swelling of pore-forming block by varying solvent(s) [27], by introducing additives to the pore-forming block [29,30,39] or by applying an external field [37].…”
Section: Membrane Fabrication Under Controlled Evaporation Conditions (By Gsnips) and Influence Of Block Copolymer Concentrationmentioning
confidence: 99%
“…Experimentally, many approaches like blending or additives in the casting solution [29][30][31][32][33][34][35][36], solution compositions [27], an electric field on as-cast polymer film [37], shear during fabrication [38,39], temperature [40], evaporation rate [41] and humidity [42] have been reported to influence the long-range order and the orientation of self-assembled nanostructures. Solvent evaporation has proven to be a remarkably effective tool for directing the self-assembled nanostructures in the block copolymer thin films.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, high-resolution contrast between microphase-separated domains can be attained [74,75]. As the ordering in such copolymers is sensitive to electric fields [44,46,48], our choice of polystyrene-block-poly(4-vinylpyridine) copolymers for the present study becomes understandable. After preliminary screening of several solvents, such as toluene, chloroform, dimethylformamide, dioxane, tetrahydrofurane, and ethanol, for vapor annealing, we chose chloroform as a good solvent for both styrene and 4-vinyl pyridine blocks and 1,4-dioxane as a selective solvent providing highest contrast between the microdomains upon vapor annealing.…”
Section: Introductionmentioning
confidence: 99%
“…The possibility of using a DC electric field for the orientation of block copolymer lamellae along the field lines was first demonstrated by Amundson et al in the early 90s [33][34][35]. Since then, the electric field effects have been investigated rather intensively Polymers 2021, 13, 3959 2 of 15 experimentally [36][37][38][39][40][41][42][43][44][45][46][47][48], by analytical/numerical theory [49][50][51][52][53][54][55][56][57][58][59][60], and via computer simulations [61][62][63]. It was demonstrated that the electric field has a strong impact on the conditions of order-disorder and order-order transitions in block copolymer melts, solutions, and thin films and can be considered as a precision tool to adjust the morphology of microphase-separated states on a nanometer scale.…”
Section: Introductionmentioning
confidence: 99%